FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT DALAM MELAKSANAKAN FUNGSI INTERMEDIASI: Studi Pada Bank Pembangunan Daerah di Indonesia - , Anaike Rizulpa Agusyanti; , I Wayan Nuka Lantara, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Local Development Bank is one of among financial institutions, functioning as an intermediary institution. As an intermediary institution, BPD accepts fund as saving deposit, time deposit and giro, which then that accepted fund would be redistributed as credit loan. This research is based on an unoptimal credit loan distribution which is done by BPD. It is viewed from Loan to Deposit Ratio (LDR) value, LDRâs rate is smaller than industrial rate value, besides that LDRâs value also under value conditioned by Bank of Indonesia (BI). So that, it needs to be examined to the factors influencing credit loan distribution on Local Development Bank (BPD), by identifiying the influences third partied fund (DPK), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA) and Net Interest Margin (NIM) to the credit loans that is proxied by Loan to Deposit Ratio (LDR). Independent variable used in this research is DPK, CAR, NPL, ROA and NIM. A dependent variable used in this research is LDR. Those samples used in this research are all Local Development Banks (BPDs). The research period from 2003 until 2011. Analysis techniques used in this research are double linear regression, meanwhile hypothesis examination uses ttest to examine the partial variable influences with significancy 5%. According to the research result gained, that DPK, ROA and NIM have a positive and significant influence to the LDR. However CAR and NPL have a negative influence to LDR. In order to make the Local Development Bank works it functions properly, then the BPD should increase lending activities especially for productive credit to the economy in that region and could become the Champion BPD according to the program initiated by Asbanda.